Kerajaan Allah Sebagai Inti Kehidupan Dan Perutusan Yesus - Martin Chen (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2012)
Abstract: The Kingdom of God is central to the whole message of Jesus Christ. Through the kingdom of God, we can discover and understand the entire mission of Jesus. The Kingdom of God is the embodiment of God’s saving presence in human life. Compared with the Jewish religious movements of that era, especially the apocalyptic movement, which also awaited the coming of the Kingdom of God, Jesus’ preaching about the kingdom of God has a special feature, that the Kingdom of God is an act of forgiveness and salvation from God, and not God’s judgment; moreover, the action is happening now in people’s life, rather than being something that is expected in the future. Through Jesus, through his word and his work, God is now present in the midst of the people. Through his parables and his words in the Sermon on the Mount and in the act of casting out demons, in healing the sick and in the forgiveness of sin, Jesus reveals the presence of a compassionate God, a God who frees people from the power of sin and leades them in the power of divine grace. Jesus not only preached the kingdom of God but gave himself so that people would experience God’s saving work. Through His death on the cross, Jesus freely poured God’s mercy and goodness upon human beings. Jesus’ proclamation of the kingdom of God has important implications for the understanding of the Christological and ecclesiological renewal. Keywords: Kingdom of God, salvation, forgiveness, word of Jesus, work of Jesus, human life, Christological and ecclesiological renewal. Abstrak: Kerajaan Allah merupakan inti seluruh pewartaan Yesus Kristus. Melalui Kerajaan Allah kita dapat menemukan dan mengerti seluruh perutusan hidup Yesus. Kerajaan Allah berarti perwujudan kehadiran Allah yang menyelamatkan dalam hidup manusia. Dibandingkan dengan gerakan keagamaan yahudi pada zaman itu, khususnya apokaliptik yang juga menantikan kedatangan Kerajaan Allah, pewartaan Yesus tentang Kerajaan Allah memiliki ciri khusus bahwa Kerajaan Allah adalah tindakan pengampunan dan penyelamatan Allah, bukan penghakiman Allah dan tindakan itu kini terjadi nyata dalam hidup manusia, dan bukannya sesuatu yang dinantikan di masa depan. Melalui diri Yesus, dalam sabda dan karya-Nya, Allah kini hadir di tengah-tengah umat-Nya. Lewat perumpamaan dan sabda bahagia maupun dalam tindakan pengusiran setan, penyembuhan orang sakit dan pengampunan orang berdosa, Yesus menyatakan kehadiran Allah yang penuh belas kasih dalam hidup manusia, yang membebaskannya dari kuasa dosa dan menuntunnya dalam kuasa rahmat Ilahi. Yesus tidak hanya memberitakan Kerajaan Allah tetapi juga memberikan diri-Nya, sehingga orang sungguh mengalami karya penyelamatan Allah. Melalui kematian-Nya di salib, Yesus mencurahkan dengan cuma-cuma kerahiman dan kebaikan Allah dalam hidup manusia. Pewartaan Kerajaan Allah Yesus ini memiliki dampak penting bagi pembaruan pemahaman kristologis dan eklesiologis. Kata-kata Kunci: Kerajaan Allah, penyelamatan, pengampunan, sabda Yesus, karya Yesus, kehidupan manusia, pembaruan pemahaman kristologis dan eklesiologis.